Alluaudite Na2Co2Fe(PO4)3 as an electroactive material for sodium ion batteries1. Issue 17 (7th May 2015) - Essehli, R.; Belharouak, I.; Ben Yahia, H.; Maher, K.; Abouimrane, A.; Orayech, B.; Calder, S.; Zhou, X. L.; Zhou, Z.; Sun, Y-K.
<x xml:space="preserve">Abstract</x> Na2Co2Fe(PO4)3 crystallizes with the alluaudite-type structure (S.G. C2/c) and plays a dual anode/cathode behavior in sodium ion batteries.